Phenomenology and philosophy of mind - Smith, David Woodruff, 1944-; Thomasson, Amie L. (Amie Lynn), 1968- (Oxford : Clarendon, 2010)
Philosophical work on the mind flowed in two streams through the 20th century: phenomenology and analytic philosophy. This volume brings them together by demonstrating how work in phenomenology may lead to significant progress of problems central to existing analytical research.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Philosophy of mind; Phenomenology